ANALYSIS OF MATHEMATICS TEXTBOOK CLASS VII ON GEOMETRY MATERIALS BASED ON THE NATIONAL EDUCATION STANDARDS AGENCY - Safrulloh Hadi Saleh; Ariantje Dimpudus; Haeruddin Haeruddin (Faculty of Teacher Training and Education, Mulawarman University, 2021)
Learning resources are one of the aspects needed to support the learning process, especially during the Covid-19 pandemic, the closest learning source to students is textbooks. Based on Permendiknas No. 2 of 2008 article 4(1), the textbooks used must meet the suitability for use based on the National Education Standards Agency. This study aims to describe the suitability of class VII mathematics textbooks used by students in Tenggarong Seberang District in terms of material aspects, namely material coverage, material accuracy, and skills. This type of research is a document/text study, the method used is the Miles and Huberman model and the validity of the data in this study was carried out by triangulation of sources and agreement percentage. The results showed that The criteria are very suitable for Mathematics textbooks SMP/MTs Class VII Revised Edition 2017, 2016 and 2014 published by the Center for Curriculum and Bookkeeping, Erlangga1), Erlangga2) with conformity indicators 19 indicators out of 24 indicators and reliability coefficient 0.91, as well as appropriate criteria for the Mathematics Assessment Book for SMP/MTs Class VII published by Erlangga with the suitability more than 14 suitability but less than 19 from 24 indicators and a reliability coefficient of 0.70.. In the sub-aspect of material coverage, the presentation of material in the Class VII SMP/MTs Mathematics books published by Erlangga1) and Erlangga2) and the Class VII SMP/MTs Mathematics Assessment Books published by Erlangga has not used a scientific approach. In the sub-aspects of material accuracy and skills, in the Mathematics Assessment Book for SMP/MTs Class VII published by Erlangga, there are items that are not in accordance with the material presented, and there are no activities that can specifically develop aspects of student skills.